How students use their libraries: A case study of four academic libraries. Issue 4 (1st October 2016) - Lopatovska, Irene; Regalado, Mariana
ABSTRACT: The purpose of this study was to explore the similarities and differences in student behavior in or uses of four academic libraries in the greater New York City area. Using on-site observations and semistructured interviews, the authors collected data about resources and tools used by students as well as their academic and nonacademic activities and contributing factors. Across all four libraries, the study identified that students were actively engaged in academic pursuits utilizing multiple library resources while working with print and digital tools. Students were also observed resting, eating, and engaging in other nonacademic activities. The variations in student behaviors across the four libraries can be explained by contextual variables that influence students' behavior in a library, including student demographics, academic requirements, work habits, and disciplinary affiliations.